2013
DOI: 10.1089/jpm.2013.0049
|View full text |Cite
|
Sign up to set email alerts
|

Finding Benefit in Bereavement among Family Cancer Caregivers

Abstract: Background and Objective: Even though cancer is the second most common cause of death, little is known about the extent to which family caregivers find meaning and benefit in the loss, and associated demographic characteristics and caregiving experiences. This study addressed this gap in our knowledge. Design and Subjects: Family caregivers participated in a nationwide survey for cancer caregivers two years after the relative's diagnosis (T1). Of those, 121 were identified as bereaved by five years postdiagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Family members who are bereaved have shown clinical levels of psychological distress and a lack of meaning in life . For example, during the 6 months after the death of their relative from cancer, 6% to 25% of bereaved caregivers have been found to meet the criteria for prolonged grief symptoms/disorder ; 7% to 40% met criteria for post‐traumatic stress disorder ; and 7% to 42% reported moderate to severe levels of depression symptoms .…”
Section: Adjustment Outcomes To Bereavement From Cancermentioning
confidence: 99%
“…Family members who are bereaved have shown clinical levels of psychological distress and a lack of meaning in life . For example, during the 6 months after the death of their relative from cancer, 6% to 25% of bereaved caregivers have been found to meet the criteria for prolonged grief symptoms/disorder ; 7% to 40% met criteria for post‐traumatic stress disorder ; and 7% to 42% reported moderate to severe levels of depression symptoms .…”
Section: Adjustment Outcomes To Bereavement From Cancermentioning
confidence: 99%
“…Transitions can lead to increased depression and anxiety, and some caregivers experience prolonged grief during bereavement (Braun, Mikulincer, Rydall, Walsh, & Rodin, 2007; Prigerson et al, 2009). Caregivers may also experience existential changes, such as finding a greater sense of meaning and purpose (Kim, Carver, Schulz, Lucette, & Cannady, 2013). It has been suggested that during the bereavement process some caregivers may experience broad changes in personality (Caspi & Moffitt, 1993; McCrae & Costa, 1993), particularly in terms of how they interact with others (Shapiro, 2001; Shear & Shair, 2005).…”
mentioning
confidence: 99%
“…Profession of a religion and high economic status were associated with willing participation in the bereaved survey, consistent with previous studies. Regarding bereavement adjustment, religion is considered an enhancer of positive effects as well as a protectant against negative impacts (29,30). In the Korean population, religion enabled bereaved families to find meaning in life after loss (31), whereas bereaved families with a lower income were at risk for poor mental health (3).…”
Section: Discussionmentioning
confidence: 99%